Pemahaman Azab Perspektif Hadis di Media Sosial: Analisis terhadap Tekstual dan Kontekstual - Dadah Dadah; Rizal Faturohman Purnama (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The phenomenon of Doom that occurs today is due to the birth of various understandings, ranging from rational understanding to irrational. This understanding comes down to blaming one element of society and social. This is because the hadith text about Doom circulating on social media today is sounded based on the motives and interests of its users. It causes differences in understanding from the source of one text. Therefore, the author is interested in studying the hadith of Doom more deeply. The stages of analysis that will be carried out in this study are linguistic analysis of hadith text which then outlines critical analysis in the form of micro and macro nuzul asbabs and contextual analysis of hadith. From the results of this study, the authors concluded that there are two typologies of understanding in interpreting the hadith of Doom, namely, the typology of normative-textual understanding. This group interprets the hadith of Doom in the final text and rejects anything beyond that. Second, the typology of contextual understanding, this group is more concerned with the context and object of a punishment without judging thoroughly. Moreover, the rise of visualization of meme content sourced from hadith teaches its users to be more selective and research the source of hadith text. In order to create a thorough and uncanny understanding